PENGARUH TEKNIK RELAKSASI GUIDED IMAGERY DAN MUROTAL AL-QUR’AN TERHADAP NYERI POST SECTIO CAESAREA - Oscar Ari Wiryansyah; Budi Kurniansyah (Jurnal Kesehatan dan Pembangunan, 2026)
Postoperative pain after cesarean section is a common problem that can inhibit maternal recovery. Pain management can be performed not only pharmacologically but also through non-pharmacological interventions, such as guided imagery relaxation techniques and Qur’anic recitation (murotal). This study aimed to determine the effect of guided imagery and Qur’anic recitation on pain reduction in post-cesarean section patients. This study employed a quasi-experimental design with a two-group pretest–posttest control approach. A total of 50 respondents were selected using purposive sampling and divided into an intervention group and a control group, each consisting of 25 respondents. Pain intensity was measured using the Numeric Rating Scale (NRS). Data were analyzed using the Mann–Whitney test. The results showed that the median pain score in the intervention group decreased from 5.00 to 3.00 after the intervention, while no change was observed in the control group (median 5.00). Statistical analysis revealed a p-value of 0.000 (p < 0.05). It can be concluded that guided imagery relaxation techniques combined with Qur’anic recitation significantly reduce pain intensity in post-cesarean section patients.